Geometric Zone-Control Algorithm for Collision and Deadlock Avoidance in AGV System - Lee, Kwanwoo; Park, Sangchul (IEEE Access, 2023)
Automated guided vehicle (AGV) system control presents several challenges, among which deadlock situations are particularly problematic, as they can significantly reduce the overall performance of the AGV system. Existing studies are based on the assumption that there is sufficient space between nodes and links in AGV guidepath topology. This study proposes a novel zone-control algorithm for AGV systems designed to prevent collisions and deadlocks. The proposed algorithm involves a zone-partitioning technique that considers both AGV geometry and guidepath topology. This method identifies all collision-prone areas and divides the AGV guidepath into zones. By effectively employing these zones, the zone-control algorithm successfully addresses and resolves deadlock problems in AGV systems. The effectiveness of the proposed algorithm was evaluated against state-of-the-art methods using irregular layouts. Experimental results demonstrated that the proposed method effectively handled delivery tasks, resulting in a 58-85% improved performance, thereby verifying its efficacy. The proposed algorithm offers a practical and effective solution for AGV systems with irregular guidepath topologies at real manufacturing sites.
Keywords: Automated guided vehicle system; Automated guided vehicles; Automated material handling systems; Collisions avoidance; Deadlock avoidance; Nodes and links; Performance; Space between; System control; Zone controls; Automated guided vehicle; automated material handling system; deadlock avoidance; zone-control